“I Don’t Know if I Am a Feminist”. Transatlantic Feminist Networks, Intellectuals and the Suffragette - Denegri, Francesca (Meridional. Revista Chilena de Estudios Latinoamericanos, 2021)
This article examines feminist responses from the Southern Cone, Peru and Spain to the increasingly visible presence of the British suffragette at the beginning of the 20th C. National Councils of Women founded in the region on the principle of Republican motherhood produced discourses marked by ambivalent politics vis a vis the “foreign” paradigm of the New Woman. The fear to transgress traditional gender mandates, exacerbated by the scorn thrown at the suffragette by leading male intellectuals in the region transverses these discourses. Given that the feminist networks built by the first generation of women writers in nineteenth century Lima and Buenos Aires have been well explored, this article purports to explore the less studied area of the legacy of this first generation of activists on to the next generation of Latin American and Spanish feminists.